2021
DOI: 10.3390/f12070910
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Defoliation on the Defense Reactions of Silver Birch (Betula pendula) Infected with Phytophthora plurivora

Abstract: In natural environments, plants develop adaptive mechanisms at the cellular and molecular levels to cope with many external factors, e.g., insects and soil pathogens. We studied physiological stress induced by different levels of foliage removal (defoliation 30% and 60%) and by infection of root rot pathogen Phytophthora plurivora on the common Polish tree species, Betula pendula, grown in an open greenhouse. This study showed that P. plurivora damaged the root system which negatively impacted all morphologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…We found that the main hotspots of the bacterium appeared after the hot and dry summer of 2010 and the following years of 2011 and 2012. Numerous works relate the distribution of this disease to changes in climatic conditions [28,30]. Moreover, among the above factors influencing the spread of the bacterium, soil conditions are also highlighted [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the main hotspots of the bacterium appeared after the hot and dry summer of 2010 and the following years of 2011 and 2012. Numerous works relate the distribution of this disease to changes in climatic conditions [28,30]. Moreover, among the above factors influencing the spread of the bacterium, soil conditions are also highlighted [27].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Zharko [31] used the red and near-infrared (NIR) bands of Sentinel-2 for a GSV estimation in the north-eastern part of Russian Kostroma region. However, the method of integrating field-based observations and remote sensing data to compare the results is considered to be the most accurate for GSV assessment [30][31][32]. An integration approach based on machine learning and multitemporal Landsat images was employed to dynamically estimate the spatial distribution of mangroves [33], where an increase in the area of trees over the 29th period was demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, trees infected with P. plurivora showed increased rates of net photosynthesis compared to those infected with P. cactorum during the growing season following the inoculation, despite the differences being not significant in all measurement days ( Ďurkovič et al., 2021 ). To this regard, it has been suggested that infected tissues can act as a carbon sink, altering plant resource allocation patterns, which can be compensated by increased photosynthetic rates ( Pagán and García-Arenal, 2018 ; Berezovska et al., 2021 ; D’Souza et al., 2021 ). In fact, several carbohydrates, including sucrose, showed an increased concentration in areas surrounding the necrotic tissues ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…A decentralized, bottom-up forest planning approach that consistently allows the cells to coevolve until the plans of all periods within the planning horizon are achieved [86] would resolve this issue. Nowakowska et al (2020a) [87] and Berezovska et al (2021) [88] studied the pathogens transmitted in soil and found that soil pathogens had a negative impact on the growth of trees. Nowakowska et al (2020b) [89] researched Norwegian spruce trees using bark beetles (IPS typographus L.) in Polish forest areas to show that insects could also threaten the growth of spruce trees.…”
Section: Conservation Gap Analysismentioning
confidence: 99%